FUTURE CITIZEN POPULATION ESTIMATES OF LIBYA - BY SEX AND AGE : 1973 - 1988 - تشارياه, د. فينكاتا (Dirasat in Economics and Business, 2022)
Population estimates for the future are very often required in economic, social, and educational planning of any country. Some population projections for Libya were made earlier, including one by the present author (Zaghloul 1970; Venkatacharya 1972). Most of the above projections are based on 1964 Census data. With some of the figures of 1973 census made available, there arises a need to make fresh population projections based on the recent demo graphic facts. This is the purpose of the present paper. The previous projections by the author (Venkatacharya, 1972) for Libya were made exclusively using the 1954 and 1964 censuses data, and it is made for the total (citizen plus alien) population of Libya as a whole. In the present work we make use of whatever figures of 1973 census are available to date along with the data of two earlier censuses. Further, we also make seperatc projections for citizen and alien populations. The citizen population is obtained by sex and age for the period 1973-88, which is presented in this paper. The projection of alien population, which is not as straight forward as projecting citizen population, is deferred to another paper.